Implementasi Program Asistensi Mengajar di Sekolah Dasar (AMSD) di SDN 14 Biru Kabupaten Bone - Sidrah; Kadir; Rukayah; Firdaus; Latri Aras (Jurnal Abdi Masyarakat Pendidikan, 2026)
The Elementary School Teaching Assistance Program (AMSD) aims to improve the competency of prospective elementary school teachers through direct involvement in various academic and non-academic activities at school. This program was implemented at SDN 14 Biru involving 10 students majoring in Elementary School Teacher Education, Faculty of Education, Makassar State University for approximately one month. The implementation method used a participatory approach that included observation, design, implementation, and reflection stages. The results of the activity showed that through AMSD, students gained real-life experiences that helped them understand their roles and responsibilities as educators. In addition, students also had the opportunity to develop creative abilities, hone pedagogical skills, and instill a resilient and disciplined attitude in students through involvement in dance training, flag ceremonies, and scouting.